Closely Related Fruit Fly Species Living at Different Latitudes Diverge in Their Circadian Clock Anatomy and Rhythmic Behavior. Issue 6 (December 2018) - Beauchamp, Marta; Bertolini, Enrico; Deppisch, Peter; Steubing, Jonathan; Menegazzi, Pamela; Helfrich-Förster, Charlotte
Recently, we reported differences in the expression pattern of the blue light-sensitive flavoprotein cryptochrome (CRY) and the neuropeptide pigment-dispersing factor (PDF) in the neuronal clock network of high-latitude Drosophila species, belonging to the Drosophila subgenus ( virilis-repleta radiation), compared with cosmopolitan D. melanogaster flies, belonging to the Sophophora subgenus. Alterations in rhythmic patterns of activity due to these differences might have adaptive significance for colonizing high-latitude habitats and, hence, adjusting to long photoperiods. Here, we show that these differing CRY/PDF expression patterns are only present in those species of the virilis-repleta radiation that colonized high latitudes. The cosmopolitan species D. mercatorum and D. hydei have a D. melanogaster -like clock network and behavior despite belonging to the virilis-repleta radiation. Similarly, 2 species of the holotropical Zaprionus genus, more closely related to the Drosophila subgenus than to the Sophophora subgenus, retain a D. melanogaster -like clock network and rhythmic behavior. We therefore suggest that the D. melanogaster -like clock network is the "ancestral fly clock phenotype" and that alterations in the CRY/PDF clock neurochemistry have allowed some species of the virilis-repleta radiation to colonize high-latitude environments.